Autologous Haematopoietic Stem Cell Transplantation for Crohn's Disease: A Retrospective Survey of Long-term Outcomes From the European Society for Blood and Marrow Transplantation. (18th May 2018) - Brierley, Charlotte K; Castilla-Llorente, Cristina; Labopin, Myriam; Badoglio, Manuela; Rovira, Montserrat; Ricart, Elena; Dierickx, Daan; Vermeire, Severine; Hasselblatt, Peter; Finke, Juergen; Onida, Francesco; Cassinotti, Andrea; et al.
Abstract: Background and Aims: Autologous haematopoietic stem cell transplantation [AHSCT] is a therapeutic option for patients with severe, treatment-refractory Crohn's disease [CD]. The evidence base for AHSCT for CD is limited, with one randomised trial [ASTIC] suggesting benefit. The aim of this study was to evaluate safety and efficacy for patients undergoing AHSCT for CD in Europe, outside the ASTIC trial. Methods: We identified 99 patients in the European Society for Blood and Marrow Transplantation [EBMT] registry, who were eligible for inclusion. Transplant and clinical outcomes were obtained for 82 patients from 19 centres in seven countries. Results: Median patient age was 30 years [range 20–65]. Patients had failed or been intolerant to a median of six lines of drug therapy; 61/82 [74%] had had surgery. Following AHSCT, 53/78 [68%] experienced complete remission or significant improvement in symptoms at a median follow-up of 41 months [range 6–174]; 22/82 [27%] required no medical therapy at any point post-AHSCT. In patients who had re-started medical therapy at latest follow-up, 57% [24/42] achieved remission or significant symptomatic improvement with therapies to which they had previously lost response or been non-responsive. Treatment-free survival at 1 year was 54%. On multivariate analysis, perianal disease was associated with adverse treatment-free survival (hazard ratio 2.34, 95% confidence interval [CI] 1.14–4.83, p = 0.02). One patient died due to infectious complications [cytomegalovirus disease] at Day +56. Conclusions: In this multicentre retrospective analysis of European centres, AHSCT was relatively safe and appeared to be effective in controlling otherwise treatment-resistant Crohn's disease. Further prospective randomised controlled trials against standard of care are warranted.